Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/10548408.2016.1167359
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Growth and the Implications for Retail Marketing Strategy: Insights from Japan

Abstract: Japan is experiencing significant growth in inbound tourist numbers, with this expected to continue. This research examines the effects of this increase on the Japanese retail sector. Tourist survey data are examined, and the level of interest and tactical marketing activity from the retail sector in targeting tourists is analyzed using a content analysis of national press sources. These findings are viewed through the lens of the literature on tourist shoppers and implications for marketing managers are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The last 5 years has seen a growth in academic research investigating Japan's tourism industry. Research has explored various facets of tourism development in Japan, including segmenting tourists on their perceptions of destinations in Japan post-disaster (Kim & Park, 2016) and tourist loyalty in post-disaster contexts (Lee & Hyun, 2016); an examination of the impact that tourism has on the Japanese retail sector (Larke, Kilgour, & John, 2016); linkages between positive perceptions that Korean tourists have of Japanese residents and their positive word of mouth recommendations (Nam, Kim, & Hwang, 2016); and the effects of the presence of Westerners at traditional Japanese historic sites on Japanese evaluations of such sites (Araya, Naoi, & Iijima, 2016). Recent research has also begun to focus specifically on the Chinese tourist market in Japan, with research predominantly drawing attention to the Chinese tourist experience.…”
Section: Tourism Development and Japanmentioning
confidence: 99%
“…The last 5 years has seen a growth in academic research investigating Japan's tourism industry. Research has explored various facets of tourism development in Japan, including segmenting tourists on their perceptions of destinations in Japan post-disaster (Kim & Park, 2016) and tourist loyalty in post-disaster contexts (Lee & Hyun, 2016); an examination of the impact that tourism has on the Japanese retail sector (Larke, Kilgour, & John, 2016); linkages between positive perceptions that Korean tourists have of Japanese residents and their positive word of mouth recommendations (Nam, Kim, & Hwang, 2016); and the effects of the presence of Westerners at traditional Japanese historic sites on Japanese evaluations of such sites (Araya, Naoi, & Iijima, 2016). Recent research has also begun to focus specifically on the Chinese tourist market in Japan, with research predominantly drawing attention to the Chinese tourist experience.…”
Section: Tourism Development and Japanmentioning
confidence: 99%
“…The results of this study are also following previous research which showed that transaction convenience which consists of aspects such as queuing time and types of payments that influence customer experience (Bagdare, 2014). According to Larke et al (2016), transaction convenience is closely related to the application of omnichannel in offline stores which has an impact on the consumer experience while shopping at the store. According to Hsu et al (2010), when consumers get comfort and convenience when transacting, they get a good experience when shopping, as well as product exchange services form a positive experience for consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Transaction convenience which consists of aspects such as queuing time and types of payments according to previous studies influences customer experience (Bagdare, 2014). According to Larke et al (2016), transaction convenience is closely related to the application of omnichannel in offline stores which has an impact on the consumer experience while shopping at the store. The positive impact for consumers of halal fashion products is that consumers feel a good experience with the time efficiency caused by the transaction process.…”
Section: Effect Of Store Attribute Transaction Convenience Dimension ...mentioning
confidence: 99%
“…The hospitality sector has grown significantly over the past 30 years as more people all over the world have high disposable incomes to travel, dine out, enjoy and experience (Larke et al, 2016;UNWTO, 2017). Today, the hospitality sector is one of the economic pillars in many countries or cities (Cárdenas-García et al, 2015;UNWTO, 2017).…”
Section: Introductionmentioning
confidence: 99%